Design and Performance Analysis of a Novel MAC Protocol for Full Duplex Wireless Network - Hongzhi Mo (Dianxin kexue)
Two independent frequency bands are used for half duplex radios to realize simultaneous transmission and reception.Recently，full duplex radios are allowed to transmit and receive data packets simultaneously in one frequency band.To improve the performance of full duplex radio networks，a novel MAC protocol called FD-MAC for full duplex radio networks，which was a simple and efficient protocol compatible with standard IEEE 802.11 MAC protocol，was proposed.By taking both the physical layer and MAC layer into account，the performance of full duplex network with FD-MAC was analyzed.The analytical and simulation results demonstrate that，compared with the existing MAC protocols for full duplex radio，FD-MAC protocol owns a higher network throughput performance and a lower power consumption.